Alveolar soft part sarcoma masquerading as lipoma: a case report - Singh, Narinder; Sharma, Vipin; Bharadwaj, Rahul; Sharma, Kavya (International Journal of Research in Orthopaedics, 2020)
We report herein, a rare case of a 14-year-old child with alveolar soft part sarcoma. The patient initially noticed a progressively growing mass over medial side of right distal thigh. Although clinically the swelling appeared to be lipoma, the needle biopsy confirmed it to be alveolar soft part sarcoma. Patient was managed by wide excision, followed by adjuvant chemotherapy.